Mothering & Psychoanalysis: Clinical, Sociological and Feminist Perspectives, edited by Petra Bueskens (Toronto: Demeter Press, 2014), 504pp., ISBN: 978-1-927335-26-0, 34.46 Paperback. Issue 1 (2015) - Briggs, Kate
No abstract available